Employment impacts of agrifood system innovations and policies: A review of the evidence - Berdegué, Julio A.; Trivelli, Carolina; Vos, Rob (International Food Policy Research Institute, 2024)
The food sector constitutes the largest global source of employment, supporting the livelihoods of most of the world’s poor and vulnerable populations. This article provides an extensive review of the available evidence of the employment effects of innovations and policy interventions in agrifood systems and value chains in low- and middle-income countries (LMICs). The review was guided by a two-part hypothesis: (1) food systems currently underperform in terms of their potential for generating decent jobs and income opportunities, and (2) this gap is only growing as expanding food markets and existing agrifood supply chain business models skew gains to the disadvantage of smallholders, agrifood small and medium enterprises (SMEs), and food sector workers.